2019
DOI: 10.1016/j.celrep.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Phosphoproteome and Transcriptome Analysis Reveals Chlamydia-Induced Epithelial-to-Mesenchymal Transition in Host Cells

Abstract: Highlights d Phosphoproteome and transcriptome analyses reveal Ctrinduced host cell signaling d Ctr causes phosphorylation of MAPK/CDK and dephosphorylation of CAMK/PKA/PKC substrates d Ctr induces epithelial-to-mesenchymal transition via ERKmediated ERF and ETS1 signaling d Ctr-induced EMT conveys host cell invasiveness and disruption of cervical epithelium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 68 publications
6
41
0
Order By: Relevance
“…Meyer and colleagues pioneered the use of ex vivo organotypic cultures and a novel fallopian tube organoid (FTO) model to investigate C. trachomatis infection in primary human epithelia 42, 43 . Partially dissected tissue from the ectocervix and fallopian tube—representing the lower and upper genital tracts, respectively—has been cultured ex vivo and infected with Chlamydia 42, 43 . These models were recently simplified by culturing isolated tubal epithelial cells in a three-dimensional matrix, generating self-renewing FTOs ( Figure 1C) 44 .…”
Section: Recent Advances In Cell Culture Infection Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meyer and colleagues pioneered the use of ex vivo organotypic cultures and a novel fallopian tube organoid (FTO) model to investigate C. trachomatis infection in primary human epithelia 42, 43 . Partially dissected tissue from the ectocervix and fallopian tube—representing the lower and upper genital tracts, respectively—has been cultured ex vivo and infected with Chlamydia 42, 43 . These models were recently simplified by culturing isolated tubal epithelial cells in a three-dimensional matrix, generating self-renewing FTOs ( Figure 1C) 44 .…”
Section: Recent Advances In Cell Culture Infection Modelsmentioning
confidence: 99%
“…More recently, a global phosphoproteomic and transcriptomic analysis in ectocervical epithelial explants infected with C. trachomatis serovar L2 indicated that infection activates cell signaling pathways to promote an EMT-like signature 43 . The infection initiates at the top of the stratified epithelia and progresses toward the basal layer, suggesting that altering cell–cell junctions during EMT may provide access for subsequent rounds of infection.…”
Section: Chlamydia Activates Epithelial-to-mesenchymal Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of SRF activity has been associated with induction of the epithelial-to-mesenchymal transition (EMT)-a process through which epithelial cells transdifferentiate into scar-forming fibroblasts [133,134]. Intriguingly, Chlamydia infection has recently been shown to induce EMT, which likely promotes the scar-forming pathology observed in chronic C. trachomatis infections [79,[135][136][137]. Could chlamydial restructuring of actin contribute to this effect?…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Much of what is known regarding Chlamydia 's mechanisms to manipulate host cells comes from in vitro studies using cancer-derived cell lines, such as HeLa cells, which provide ease of maintenance and genetic manipulation, but lack much of the relevance of an in vivo environment (Dolat and Valdivia, 2019 ). Beyond cancer-derived cell lines, immortalized and polarized cell lines of reproductive tissues have broadened the relevance of in vitro systems (Igietseme et al, 1994 ; Guseva et al, 2005 , 2007 ; Moore et al, 2008 ; King et al, 2009 ), and primary cells have provided systems with minimal artificial manipulation of cells (Prozialeck et al, 2002 ; Roth et al, 2010 ; Zadora et al, 2019 ; Maffei et al, 2020 ). Further, the use of three-dimensional (3D) and multi-cell type models have allowed for incorporating aspects of cell-cell interactions and tissue architecture (Nogueira et al, 2017 ; Edwards et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%